Analysis on index of Remaining Carrying capacity of host community to tourism development (case study: shahroud city) - Sajad ferdowsi; Najmeh Nazari Mazidi; Mehdi Modudi Arquhdi (تحقیقات کاربردی علوم جغرافیایی)
This study was conducted to estimate the index of Remaining carrying capacity of host community to tourism development. The method of data analysis is descriptive-analytical. In order to collect the initial data, a field survey and a questionnaire were used. The study population is comprised of specialists related to the subject and residents of Shahroud (host community). The sample size for distribution of the host community questionnaire is 125 people (65 inhabitants, 41 tourism business owners, 19 officials). In this regard, 20 questionnaires have been considered for the survey of experts. Method of determining the carrying capacity of the host community in the study adapted of Battelle Environmental Evaluation System (BEES) that it is used for environmental impact assessment (EIA) and the limits of acceptable change (LAC). The results of data analysis showed that based on barometer of sustainability Alan Prescott, and according to the parameters obtained by (0.426), carrying capacity of the host community, by positioning the floor of 0.41 to 0.60 of the situation is balanced state. Therefore, it is understood that the host society has a balanced attitude towards tourism and is not opposed to its development. As a result, it is essential to use existing potentials in order to sustainable tourism development, necessary planning should be made by tourism managers to attract more tourists to this area.